2017
DOI: 10.1128/mcb.00060-17
|View full text |Cite
|
Sign up to set email alerts
|

Multiplication of Ribosomal P-Stalk Proteins Contributes to the Fidelity of Translation

Abstract: The P-stalk represents a vital element within the ribosomal GTPaseassociated center, which represents a landing platform for translational GTPases. The eukaryotic P-stalk exists as a uL10-(P1-P2) 2 pentameric complex, which contains five identical C-terminal domains, one within each protein, and the presence of only one such element is sufficient to stimulate factor-dependent GTP hydrolysis in vitro and to sustain cell viability. The functional contribution of the P-stalk to the performance of the translationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 71 publications
2
25
1
Order By: Relevance
“…In our analyses, the dynamics of the C-terminal uL10 variants, irrespective of the modifications tested, resembled that of the wild-type, showing that this region has no role in the interplay of uL10 with the ribosome. In line with this observation are published data showing that this C terminus represents a critical part of the ribosomal stalk, which governs the interaction with translational GTPases or RIPs [31,70,71] and plays a decisive role in the biological activity of P-proteins [25]. Importantly, our recent analyses indicate that the phosphorylation of the C terminus significantly influences the kinetics of the interaction between stalk proteins and external factors (personal communication from M. Tchorzewski, 2020).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…In our analyses, the dynamics of the C-terminal uL10 variants, irrespective of the modifications tested, resembled that of the wild-type, showing that this region has no role in the interplay of uL10 with the ribosome. In line with this observation are published data showing that this C terminus represents a critical part of the ribosomal stalk, which governs the interaction with translational GTPases or RIPs [31,70,71] and plays a decisive role in the biological activity of P-proteins [25]. Importantly, our recent analyses indicate that the phosphorylation of the C terminus significantly influences the kinetics of the interaction between stalk proteins and external factors (personal communication from M. Tchorzewski, 2020).…”
Section: Discussionsupporting
confidence: 73%
“…The primary role of the P-stalk is interaction with translational GTPases and stimulation of their GTPase activity during each step of translation [18][19][20][21][22][23][24]. The phenomenon of multiplication of P-stalk proteins was functionally linked with the decoding event, thus associating the stalk also with translational fidelity [25]. The stalk proteins were named P-proteins [26], because they are phosphorylated by CK2 protein kinase at their conserved C termini [27][28][29], that is, a protein element that is regarded as a functional region responsible for direct interactions with translational factors or ribosome-inactivating proteins [23,24,30,31].…”
mentioning
confidence: 99%
“…During cytosolic LSU maturation in yeast, a RLP24 placeholder protein is replaced by RP eL24, then RP uL16 is added and P-stalk assembly is initiated in parallel to or after Rei1 action ( Meyer et al., 2010 ). The P-Stalk is a pentameric uL10-(P1-P2) 2 complex in yeast ( Wawiórka et al., 2017 ), with additional P3 components in plants, that assists translation associated GTPases. For P-stalk assembly, Yvh1 mediates the release of Mrt4, a placeholder for uL10, and enables substitution by functional uL10 ( Zhou et al., 2019 ).…”
Section: Assembly Of Heterogeneous Ribosomesmentioning
confidence: 99%
“…N-domain (rRNA-anchoring domain) anchors the arm proteins at GTPase-associated center in the large subunit of ribosome, whereas C-domain is a helical spine to bind multiple copies of arm proteins. Each arm protein hands translational GTPases and recruits them to the ribosome, and it was reported that copies of arm protein involve in both efficiency and fidelity of translation ( 10 , 14 ). Although the rRNA-anchoring domains of P0 and L10 have similar structures, the helical spines have different conformations, which are consistent with the structural difference between aP1 (P1•P2) and L12.…”
Section: Introductionmentioning
confidence: 99%